2023
DOI: 10.1371/journal.pntd.0011284
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of Aspergillus seropositivity and chronic pulmonary aspergillosis in an urban tertiary hospital in Sierra Leone: A cross-sectional study

Abstract: Background In the World Health Organization Global Tuberculosis (TB) Report 2022, 37% of pulmonary TB patients were clinically diagnosed and thus many people were treated for TB without evidence of the disease. Probably the most common TB misdiagnosis is chronic pulmonary aspergillosis (CPA). In this study, we aimed to assess the prevalence and predictors of Aspergillus seropositivity and CPA in patients with chronic respiratory symptoms in an urban tertiary hospital in Sierra Leone. Methodology/principal fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…79 In a recent cross-sectional study in an urban tertiary hospital in Sierra Leone, current or past TB infection (odds ratio: 3.52) was an independent predictor of Aspergillus seropositivity and CPA. 80 Risk factors for CPA in patients with active TB are age > 40 years, smoking, diabetes, low body mass index, male sex, steroid use, and cavitary disease. 6 The frequency of hemoptysis in PTLD patients with CPA was reported to be high ranging from 20 up to 68%.…”
Section: Clinical Presentation Of Chronic Pulmonary Aspergillosis In ...mentioning
confidence: 99%
“…79 In a recent cross-sectional study in an urban tertiary hospital in Sierra Leone, current or past TB infection (odds ratio: 3.52) was an independent predictor of Aspergillus seropositivity and CPA. 80 Risk factors for CPA in patients with active TB are age > 40 years, smoking, diabetes, low body mass index, male sex, steroid use, and cavitary disease. 6 The frequency of hemoptysis in PTLD patients with CPA was reported to be high ranging from 20 up to 68%.…”
Section: Clinical Presentation Of Chronic Pulmonary Aspergillosis In ...mentioning
confidence: 99%
“…Of these, approximately 1.2 million cases are thought to be due to previously treated PTB. Recent estimates from Africa has shown that PTB accounts for over 60% of underlying disease among over 1,200 published cases of CPA across the continent [14][15][16]. A recent study in India estimated an annual incidence of 363,601 cases of CPA associated with PTB and 42,766 deaths, accounting for 11% of total PTB deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Our current understanding of the spectrum of CPA in a population of PTB patients has broadened, with observational studies showing that CPA occurs in about 8% of patients being treated as smear-negative or PTB relapse [7], 4 to 20% in early PTB or end of PTB treatment and in patients with persistent symptoms despite optimal anti-tuberculous treatment [8,10,14,18], and 1 to 54% post-PTB treatment [6,8,9,11,13,14,19].…”
Section: Introductionmentioning
confidence: 99%